The Role of Compensation and Loyalty to Employee Turnover Intention - Suhardi, Agatha Rinta; Oktari, Sari Dewi (Universitas Pamulang, 2023)
High turnover intention can indicate an ineffective organization because the company loses experienced employees and needs to retrain new employees. In addition, the high level of turnover intention will create instability and uncertainty about labor conditions and increase the cost of human resources. The purpose of this study was to determine the effect of compensation and loyalty on employee turnover intention by using a saturated sampling technique in sampling. Data processing was carried out by analyzing correlation coefficients, coefficients of determination, and hypothesis testing. The results of this study indicate that compensation has a strong relationship with turnover intention and has a significant negative effect on the turnover intention variable, which means that if compensation is increased, turnover intention will decrease. Another result is that loyalty has a strong relationship with turnover intention and has a significant negative effect on turnover intention, which means that if employee loyalty increases, turnover intention will decrease. Compensation and loyalty have a very strong relationship with turnover intention, the higher the compensation and loyalty, the lower the turnover intention.